Pengaruh Kegiatan Rohani Islam (Rohis) Dan Pembinaan Akhlak Terhadap Kepemimpinan Siswa Di MAN Berau - Neni Hariyani Hairunnisa; Dayu Sumantoro; Siti Maryam; Muhammad Alfi Syahrin (Educational Research Center, 2026)
Student leadership is an important aspect of character development in schools and can be strengthened through Islamic Spiritual Activities (Rohis) and moral guidance programs. This study aims to analyze the influence of Rohis activities and moral guidance on student leadership at MAN Berau. The research employed a quantitative approach with a multiple linear regression method involving students participating in Rohis activities and moral guidance programs, with data collected through questionnaires, observations, and documentation and analyzed using SPSS. The results showed that Rohis activities and moral guidance significantly influence student leadership both partially and simultaneously, with a coefficient of determination (R Square) of 0.611, indicating that 61.1% of student leadership is explained by these two variables.